Evaluation of Cyto-Genotoxic Effects of Mucuna Bracteata DC. Ex Kurz Leaf Extracts by Allium Cepa - Chowdhury, Muntasir Ahmed; Biswas, Animesh (Journal of Bio-Science, 2024)
This study was conducted to evaluate the cyto-genotoxicity of leaf decoctions of Mucuna bracteata by Allium cepa bioassay. This kind of study can be used as a baseline monitoring system for plant products before their use. It is an inexpensive, simple, and reliable test to determine the cytotoxic and genotoxic effects of various plant extracts on living organisms. In this experiment, Allium cepa bulbs were placed in five concentrations (0.5 mg/mL, 2.5 mg/mL, 5.0 mg/mL, 7.5 mg/mL, and 10.0 mg/mL) of leaf decoction, with tap water as the negative control and 20.0 µL/L EMS (Ethylmethene sulphonate) as the positive control. Each concentration had five replicates. The cyto-genotoxicity assay exhibited a dose-dependent influence on the mitotic index. The mitotic index of the negative control and the positive control were 16.8 ± 0.37% and 6.86 ± 1.71%, respectively. The lowest dose of the extract, 0.5 mg/mL, had the highest mitotic index (14.2 ± 0.73%), while the highest dose, 10.0 mg/mL, had the lowest (9.6 ± 0.40%), and all indices were significantly higher than the positive control. Except for the 10 mg/mL concentration, the mitotic indices of other concentrations were significantly lower than the negative control. Different types of chromosome disorders, namely, disorderly prophase, sticky chromosomes, chromosome bridges, laggard chromosomes, pole deviation, vagrant chromosomes, nuclear filaments with terminal expansion, c-mitosis, micronuclei, and elongated nuclei, were observed. Various changes in root size, growth, and color were revealed by macroscopic examinations. Tumors were formed in roots at the highest doses but not at lower concentrations. Therefore, M. bracteata leaf extract showed cytotoxic and genotoxic effects on the Allium root meristem. J. Bio-Sci. 32(2): 71-82, 2024